410 Total Hospital Cost of Middle Meningeal Artery Embolization Compared to Surgery for Chronic Subdural Hematomas: A Propensity Matched Analysis. (1st March 2022) - Catapano, Joshua; Srinivasan, Visish M.; Koester, Stefan; Rumalla, Kavelin; Baranoski, Jacob F.; Rutledge, Caleb; Cole, Tyler S.; Winkler, Ethan A.; Lawton, Michael T.; Jadhav, Ashutosh; Ducruet, Andrew F.; Albuquerque, Felipe
Abstract : INTRODUCTION: Fewer treatment failures have been found with middle meningeal artery (MMA) embolization compared to surgical evacuation for chronic subdural hematomas (cSDH). METHODS: All patients who presented with a cSDH to a single center from January 1st, 2018 to December 31, 2020 were retrospectively reviewed. Patients with one-year of post-treatment hospital cost data were included. Patients were placed into two cohorts based on initial treatment: surgery versus MMA embolization. Total hospital cost was obtained by the hospital financial department. A propensity match analysis(matching for age, sex, Charlson Comorbidity Index(CCI), presenting symptoms, previous trauma, use of pre-operative anticoagulants/antiplatelets(AC/AP), and maximal diameter of cSDH on pre-treatment CT image) was performed. The primary outcome was the mean hospital cost difference between surgery and MMA embolization after propensity match analysis. RESULTS: One-hundred-and-seventy patients met inclusion criteria, 48(28%) in the MMA and 122(72%) in the surgical cohort. There was no significant difference between the groups in mean age, CCI, preoperative AC/AP use, and initial presenting symptoms. The surgical cohort was found to have larger pre-treatment cSDHs (20.5mm, sD 6.7) and longer index hospital admissions (9.8 days, sD 7) compared to the MMA cohort(cSDH size:16.9 mm, sD 4.6; hospital days: 5.7, sD 2.4) (p<0.001). A higher percentage of patients in the surgical cohort required an unplanned additional hematoma treatment (N=20, 16.4%) and hospital readmission(N=34, 28%) compared to the MMA group (additional treatment and hospital readmission:N=2, 4%)(p=0.04 and p=0.004, respectively). There was no significant difference in complications between the two cohorts. After propensity matching, the total hospital cost for the surgical cohort(N=28, 59, 809, sD 27, 730) was significantly higher compared to MMA embolization (N=28, 44, 273, sD 17, 622) (p=0.015). Linear regression analysis found an unexpected additional treatment as the only variable significant for total hospital cost in the match cohort (difference of 20, 772, sD 10, 037) (p=0.04). CONCLUSION: MMA embolization is associated with a decreased hospital cost compared to surgery. This lower cost is directly related to the decreased need for additional treatment interventions in the MMA group. This analysis further supports the overall clinical and financial efficacy of MMA embolization in select cSDH patients.